Urgensi Pembaharuan Undang-Undang Kepailitan Demi Efisiensi dan Keadilan dalam Penyelesaian Kepailitan dan PKPU - Hs, Fatimah; Aryani Manangin, Susi; Octavianus Nasirun, Indrasatya; Marlina Pasla, Delma (Zaaken: Journal of Civil and Business Law, 2024)
This research aims to examine the application of the KPKPU Law, as well as the urgency of renewing the KPKPU Law. this type of research uses normative juridical research. the data source of this research pays attention to, examines, and knows the application of legal principles. in the application of the KPKPU Law, there is a discrepancy with the purpose of the birth of bankruptcy law. Since the enactment of the Bankruptcy Law, filing for bankruptcy against debtors seems to have been made easier, which has resulted in many debtors being declared bankrupt. In addition, the PKPU time limit is very fast. Therefore, if PKPU is filed by a creditor, the debtor is required to submit a peace proposal to all creditors. In practice, due to force majeure, it is not uncommon for debtors to default less than a year after the approval of the peace plan. Bankruptcy law should not only pay attention to creditors and debtors, but more importantly pay attention to the interests of stakeholders, which in this case the most important is workers. In order for the effectiveness of bankruptcy law to be realized fairly, it is necessary to refresh the KPKPU Law.